Influence of carbon-dioxide concentration on human well-being and intensity of mental work - Kajtar, Laszlo; Herczeg, Levente (Idoejaras, 2012)
In the frame of experiments carried out at the Department of Building Service Engineering and Process Engineering of Budapest University of Technology and Economics BUTE the impact of CO sub(2) concentration in the air was examined. Subjects' well-being was evaluated by the aid of subjective scales, physiological variables were recorded, and subjects' mental performance was measured by a standard test. Results obtained in the experiments show that subjects evaluated air quality is less acceptable, more unpleasant, and became more exhausted when the CO sub(2) concentration increased up to 3000 ppm. 3000 ppm CO sub(2) concentration in the air proved to be less advantageous for mental performance than 600 ppm. Several physiological measures show that a mental task requires a greater effort from the subjects when the CO sub(2) concentration in the air reaches 3000 ppm. It was shown that human well-being as well as the capacity to concentrate attention are declining when subjects spend 2 to 3 hours in a closed space with 3000 ppm or higher CO sub(2) concentration in the air. Standards accurately prescribe the values of fresh air, breathing, and inside air quality assuring the health protection at workplaces. We examined the level of carbon-dioxide concentration above which the efficiency of mental work and the human well-being significantly declines.